Wanted - women's empowerment guidelines to fight food crisis - Haan, Nicoline C. de (Devex, 2022)
At the current rate, the world will not achieve gender equality for another 300 years. This lack of progress is holding back food systems and contributing to the current food crisis. Recent assessments found that women’s chances of being food insecure were about 27% higher than men’s globally. Considering this gap is expected to rise given the current state of the global food system, one critical step is establishing women’s empowerment guidelines to help countries combat the looming food crisis.